The whispering trees - White, J. A. (White, J. A. Thickety., 2016)
Chased by the demon Sordyr into a dark forest, Kara and Taff meet Mary Kettle, a witch seeking redemption from her past. Mary offers to teach Kara to use her magic without the cumbersome need for a grimoire--but it may be a dark trap, as Mary may not be as redemption-seeking as she proclaims.